PERAN PENGADILAN MILITER II-11 YOGYAKARTA DALAM MEMUTUS PERKARA DESERSI MILITER - , MULYADI SANTOSO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose that author make of this title because of the interest raised by the military discipline always seen in all things, but in fact many military soldiers got disciplined over indiscipline, but not deterrent punishment meted out discipline to commit the crime of desertion. The purpose of the authors do these street vendors as an ingredient to make a final report and a requirement for graduation from 3 Diploma in Law UGM, to continue their education to a higher level, as well as an experience gained in college yet. The benefits of those street vendors authors have new experiences working with the command system, knowledge that has not been obtained in college, as well as knowing how soldiers were tried by a military court. Is on 60 percent of military members who commit criminal acts have previously Desertion get disciplined soldiers in his unit. Under Law No. 26 Year 1997 Article 8 of disciplinary punishment at form of a reprimand, lightweight detention no later than 14 (fourteen) days, severe detention later than 21 (twenty one) days by Ankum. Hearing and deciding cases will finished with or without the presence of (in absentia) the defendant before the trial, defendant can be sentenced to imprisonment principal and additional punishment of dismissal from his service. The dismissal of the defendant due to his service aggravating factors such as the defendant has not been found. Factors that cause the crime of desertion under Article 87, 88, 89 the Code of Military Criminal Law (KUHPM) there are two factors and the factors is internal factors and external factors.